Finite element formulation for Maxwell's equations with space dependent electric properties: Application to time domain reflectometry probe - Chambarel, Andre; Ferry, Evelyne (European Journal of Computational Mechanics, 2000)
The Time Domain Reflectometry -TDR- probe is a new technique applied to moisture measurement. It is a wave guide constituted by two or three parallel metallic rods stuck in the ground. An electromagnetic wave propagates all along the wave guide and crosses a variable electric properties medium. In that way the reflecting wave is disrupted and we detect the electric singularities. We study the transverse magneti- mode. We simulate this wave guide in this medium thanks to the Finite Element Method and present the used matricial structure. For time integration we compare a semi-implicit or Runge-Kutta method with variable time-step. This process is driven by the Automatic Multigrid System with an unknown time-dependent number ..